Regional Estimation of Low Flows for Mazandaran River Basin - S. S. Eslamian; A. Zarei; A. Abrishamchi (Tulīd va Farāvarī-i Maḥṣūlāt-i Zirā̒ī va Bāghī, 2004)
An approach for regional low flow frequency analysis is to use multiple regression techniques for obtaining relationships between low flows with specific return periods and catchments characteristics. In this paper, this method has been used. After single-site frequency analysis for 20 stream gauging stations, homogeneity test was performed. Regional relationships between low flows with return periods 2 , 5 , 10, and 20 years and catchments characteristics were derived. For this purpose, catchment area, mean elevation, minimum elevation, shape factor, main channel length, length of main chanel from catchment centroid to outlet, forest area, mean annual rainfall, and mean catchment slope as model inputs were examined and cachment area, mean elevation, and mean catchment slope entered to the models. Finally, the mean relative error of models for different return period, 2, 5, 10, and 20 years, was computed 41.1, 41.3, 45.0, 47.2 percent, respectively that in comparison with other studies, it displays smaller errors.